(untitled) (International Journal of Innovative Research in Computer Science & Technology, 2017)
Cloud computing is the emerging era in many fields of computing. Here the major role is that storing of user data and data has to provide to the users whenever they needed. There are many challenges will takes place to perform store and providing of information to the user. One of the challenges in cloud computing is the integrity of the data stored in cloud. Here we are identifying existing techniques which are used for data integrity checking in cloud computing.